160k views
0 votes
Isabel graphed the following system of equations.

2x – y = 6

y = -3x + 4



She came up with the solution (2,-2).

What were the 3 steps she did to get that solution? (Make sure they are in the correct order)

1)_______________________
2)_______________________
3)_______________________

User Diimdeep
by
5.9k points

1 Answer

2 votes

Answer:


Explanation:

1) She solved the first equation for x:


2x - y = 6\\\\2x= 6+y\\\\x = (6+y)/2

2) Plug x into the second equation:


y = -3x + 4\\y = -3((6+y)/2) + 4\\\\y - 4 = (-18 -3y)/2\\2y - 8 = -18 - 3y\\5y -8 = -18\\5y = - 10\\y = -2

3) Plug y into the first equation to find x:


2x - y = 6\\\\2x - (-2) = 6\\\\2x+2=6\\\\2x = 4\\x=2


Complete the interval: (2, -2)

User Lastcanal
by
5.9k points